PERLINDUNGAN HUKUM TERHADAP HAK ISTRI DALAM PERKAWINAN MENURUT HUKUM POSITIF DI INDONESIA - Bobby Trisna Darmawan; Fitria Agustin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Marriage is a legal institution that not only regulates the personal relationship between husband and wife but also gives rise to legal consequences regarding the rights and obligations of the parties. In practice, inequalities in the fulfillment of rights are still frequently encountered, particularly concerning the wife. This study aims to analyze the forms of legal protection for the wife's rights in marriage under positive law in Indonesia as well as its implementation in society. The research method used is normative juridical, employing a statutory approach and a conceptual approach. The results of the study indicate that legal protection for the wife has been regulated in Law Number 1 of 1974 concerning Marriage as amended by Law Number 16 of 2019, as well as in the Compilation of Islamic Law. However, in practice, obstacles such as cultural factors, economic conditions, and lack of legal understanding still exist. Therefore, it is necessary to enhance legal awareness and optimize law enforcement to ensure the fulfillment of the wife's rights in marriage.